Glycine Receptors in CNS Neurons as a Target for Nonretrograde Action of Cannabinoids - Lozovaya, Natalia (J Neurosci, 2005)
At many central synapses, endocannabinoids released by postsynaptic cells act retrogradely on presynaptic G-protein-coupled cannabinoid receptors to inhibit neurotransmitter release. Here, we demonstrate that cannabinoids may directly affect the functioning of inhibitory glycine receptor (GlyR) channels. In isolated hippocampal pyramidal and Purkinje cerebellar neurons, endogenous cannabinoids anandamide and 2-arachidonylglycerol, applied at physiological concentrations, inhibited the amplitude and altered the kinetics of rise time, desensitization, and deactivation of the glycine-activated current (I(Gly)) in a concentration-dependent manner. These effects of cannabinoids were observed in the presence of cannabinoid CB1/CB3, vanilloid receptor 1 antagonists, and the G-protein inhibitor GDPβS, suggesting a direct action of cannabinoids on GlyRs. The effect of cannabinoids on I(Gly) desensitization was strongly voltage dependent. We also demonstrate that, in the presence of a GABA(A) receptor antagonist, GlyRs may contribute to the generation of seizure-like activity induced by short bursts (seven stimuli) of high-frequency stimulation of inputs to hippocampal CA1 region, because this activity was diminished by selective GlyR antagonists (strychnine and ginkgolides B and J). The GlyR-mediated rhythmic activity was also reduced by cannabinoids (anandamide) in the presence of a CB1 receptor antagonist. These results suggest that the direct inhibition of GlyRs by endocannabinoids can modulate the hippocampal network activity.